A phylogenetic study of the genus Silene in North Africa - Melilia Mesbah; Ntwai A. Moiloa; Llorenç Sáez; Javier López-Alvarado; Gianluigi Bacchetta; Ridha El Mokni; Lorenzo Peruzzi; Farid Bekdouche; Errol Véla; Mohamed Sahnoune; Bengt Oxelman (Plant Systematics and Evolution, 2026)

The importance of blood trace elements in the biomonitoring of agrochemicals exposure and effects on DNA and epigenetic alterations - Ingrid M. Flesch; Shanda A. Cattani; Daiane Domingues; Caroline P. Peruzzi; Paula Rohr; Ana Letícia H. Garcia; Rafael Moreira; Mariele F. Charão; Juliana Da Silva; Gabriela Göethel; Marcelo Arbo; Adriana Gioda; et al. (Journal of Trace Elements in Medicine and Biology, 2025)

The efficacy of cognitive stimulation, cognitive training, and cognitive rehabilitation for people living with dementia: a systematic review and meta-analysis - Alice Paggetti; Ylenia Druda; Francesco Sciancalepore; Francesco Della Gatta; Antonio Ancidoni; Nicoletta Locuratolo; Paola Piscopo; Luca Vignatelli; Luciano Sagliocca; Antonio Guaita; Piero Secreto; Andrea Stracciari; et al. (GeroScience, 2024)
Cognition-oriented treatments (COTs) are a group of non-pharmacological treatments aimed at maintaining or improving cognitive functioning. Specific recommendations on the use of these interventions in people living with dementia (PLwD) are included in the Italian Guideline on the Diagnosis and Treatment of Dementia and Mild Cognitive Impairment, developed by the Italian National Institute of Health. This systematic review and meta-analysis, based on the GRADE methodology, is part of the guideline. Considered outcomes included the cognitive functions, quality of life, and functional abilities of PLwD, taking into account disease severity, modality and system of delivery, and form of the intervention. The effectiveness of these interventions on caregivers’ outcomes was also assessed. Both group and individual cognitive stimulation were reported as effective in supporting cognitive functions in PLwD at any degree of severity. Individual cognitive training and group cognitive training were reported as effective in improving global cognitive functions in people with mild dementia. Cognitive rehabilitation appeared to be effective only in improving the functional abilities of people with mild dementia. Cognitive rehabilitation appeared to be the most effective in improving caregivers’ outcomes, with results suggesting a reduction in care burden. The observed differences in the effectiveness of these interventions in people with different disease severity can be explained by the intrinsic characteristics of each intervention. Despite the large number of available studies, a high clinical, statistical, and methodological heterogeneity was observed. More methodologically rigorous studies are needed to clarify the effectiveness of each protocol and modality of intervention.

Seed morphological variation in four closely related Linaria species (Plantaginaceae) endemic to the Tyrrhenian area - M. Sarigu; M. Ucchesu; A. Carta; L. Peruzzi; G. Bacchetta (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; G. Calvia; et al. (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

Evaluating longitudinal dispersion of scalars in rural channels of agro-urban environments - Cosimo Peruzzi; Andrea Galli; Enrico A. Chiaradia; Daniele Masseroni (Environmental Fluid Mechanics, 2021)
In agro-urban environments, the water resource conveyed by rural channels is susceptible to a gradual impoverishment due to the continuous combined sewer overflow release, constituting a pending and urgent issue for water management companies and the entire community. Reliable one-dimensional longitudinal dispersion coefficients D are required to model and study the hydrodynamics and water quality patterns at the scale of rural channel networks. Empirical formulas are usually adopted to estimate D but the accuracy in the prediction could be questionable. In order to identify which are the most suitable formulas to determine D in rural channels, field tracer measurements were carried out in three rural channels with typical geometry and configuration. The obtained D values were then compared with the most commonly used predicting formulas that the literature provides. The accuracy of the predictors was further checked by simulating different flow rates inside the tested channels by using a one-dimensional hydraulic model. Starting from the obtained results, indications and guidelines to choose the most suitable formulas to predict D in rural channels were provided. These indications should be followed when developing realistic quality models in the agro-urban environments, especially in those cases where direct measurements of the longitudinal dispersion coefficient D are not available.

Narrow endemic species Bellevalia webbiana shows significant intraspecific variation in tertiary CSR strategy - G. Astuti; D. Ciccarelli; F. Roma-Marzio; A. Trinco; L. Peruzzi (Plant Biosystems, 2019)

A Regulatory Circuitry Between Gria2, miR-409, and miR-495 Is Affected by ALS FUS Mutation in ESC-Derived Motor Neurons - Davide Capauto; Alessio Colantoni; Lei Lu; Tiziana Santini; Giovanna Peruzzi; Silvia Biscarini; Mariangela Morlando; Neil A. Shneider; Elisa Caffarelli; Pietro Laneve; Irene Bozzoni (Molecular Neurobiology, 2018)

An updated checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; N. M. G. Ardenghi; E. Banfi; L. Celesti-Grapow; A. Albano; A. Alessandrini; G. Bacchetta; S. Ballelli; M. Bandini Mazzanti; G. Barberis; et al. (Plant Biosystems, 2018)

An updated checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Albano; A. Alessandrini; N. M. G. Ardenghi; G. Astuti; G. Bacchetta; S. Ballelli; E. Banfi; G. Barberis; L. Bernardo; et al. (Plant Biosystems, 2018)

Effects of UV radiation and rainfall reduction on leaf and soil parameters related to C and N cycles of a Mediterranean shrubland before and after a controlled fire - L. Díaz-Guerra; D. Verdaguer; M. Gispert; G. Pardini; J. Font; J. A. González; E. Peruzzi; G. Masciandaro; L. Llorens (Plant and Soil, 2018)

Chromosome diversity and evolution in Allium (Allioideae, Amaryllidaceae) - L. Peruzzi; A. Carta; F. Altinordu (Plant Biosystems, 2017)

The avoidance of self-interference in the Tuscan endemic spring geophyte Crocus etruscus Parl. (Iridaceae) - A. Carta; S. Campigli; L. Peruzzi; G. Bedini (Plant Biosystems, 2016)

All in an afternoon: mixed breeding system in one-day lasting flowers of Hypericum elodes L. (Hypericaceae) - A. Carta; L. Savio; G. Bedini; L. Peruzzi; A. Fisogni; M. Galloni (Plant Biosystems, 2016)

Three new hybrids of Ophioglossum (Ophioglossaceae) from Monte Pisano, Tuscany (Central Italy) - L. Peruzzi; B. Pierini; S. Magrini; A. Andreucci; D. Marchetti; R. Viane (Plant Biosystems, 2015)

Are Red Lists really useful for plant conservation? The New Red List of the Italian Flora in the perspective of national conservation policies - G. Rossi; C. Montagnani; T. Abeli; D. Gargano; L. Peruzzi; G. Fenu; S. Magrini; M. Gennai; B. Foggi; R.P. Wagensommer; S. Ravera; A. Cogoni; et al. (Plant Biosystems, 2014)

Phylogenetic relationships of Italian Bellevalia species ( Asparagaceae ), inferred from morphology, karyology and molecular systematics - A. Borzatti Von Loewenstern; T. Giordani; G. Astuti; A. Andreucci; L. Peruzzi (Plant Biosystems, 2013)

Does Plantago brutia Ten. (Plantaginaceae) merit specific rank? Insights from nrDNA and cpDNA data - A. M. Palermo; A. De Vita; L. Peruzzi; D. Gargano; L. Bernardo; A. Musacchio (Plant Biosystems, 2010)

Gagea bohemica (Liliaceae), a highly variable monotypic species within Gagea sect. Didymobulbos - A. Peterson; D. Harpke; L. Peruzzi; J.‐M. Tison; H. John; J. Peterson (Plant Biosystems, 2010)

Phylogenetic relationships of Gagea Salisb. (Liliaceae) in Italy, inferred from molecular and morphological data matrices - L. Peruzzi; A. Peterson; J.-M. Tison; J. Peterson (Plant Systematics and Evolution, 2008)